Quality of Life (QOL) of Balinese Women Working in Spa Tourism Industry - Putu Sucita Yanthy; Luh Gede Leli Kusuma Dewi; W. Citra Juwitasari (Institut Pariwisata dan Bisnis Internasional, 2015)
Bali is one of spa tourist destinations having various categories of spas and spa treatments, and the most important is the spa therapists. Spa development becomes an interesting phenomenon to be studied when it is associated with an involvement of Balinese women as spa therapists in foreign countries. The world’s demand for Balinese spa therapists has become the motivation of women to work in this area. The work and life of Balinese spa therapists while they are working in foreign countries serve as parameters to know their quality of life, and these parameters are also the main focus of this study. Through in-depth interviews and questionnaires distributed to 20 therapists it was found out that 85 percent of them have revealed an improvement in their quality of life that is influenced by two factors: the material and intimacy factors. The material factor in question refers to the economic improvement of the family as they could earn enough income to cover their family needs. The intimacy factor in question refers to closeness and a sense of solidarity fostered while they are working abroad and the relationship within the family. This study concludes that the most important part of the development of spa in Bali is its female Balinese spa therapists due to the image that Balinese women working as spa therapists are loyal, hard-working and honest making them in demand among tourists who are seeking spa treatments. Being a spa therapist can improve their quality of life, which means that subjectively both material and intimacy factors are the aspects that affect the quality of life of the Balinese spa therapists.